Study on the physicochemical properties and immunomodulatory anti-tumor effect of the Pholiota adiposa polysaccharide. Issue 9 (14th April 2022) - Yang, Zhongwei; Liu, Zijing; Xu, Jie; Zhu, Junmo; Pu, Youwei; Bao, Yixi
Abstract : In this study, the extraction, purification, physical and chemical properties, and biological activity of the Pholiota adiposa (PAP) polysaccharide were investigated. Abstract : In this study, the extraction, purification, physical and chemical properties, and biological activity of the Pholiota adiposa (PAP) polysaccharide were investigated. One fraction (PAP-1a) of Pholiota adiposa polysaccharides was isolated using DEAE Sepharose™ Fast Flow and Sephacryl™ S-300 High-Resolution columns. The HPLGPC results revealed that the molecular weight of PAP-1a was 16.453 kDa. PAP-1a was composed of mannose, ribose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, xylose, arabinose, and fucose and their molar % was 33.41, 0.53, 1.33, 0.07, 0.27, 5.28, 38.31, 0.83, 18.04 and 2.23, respectively. PAP-1a could activate macrophages to secrete NO and cytokines such as TNF-a, IL-6, and IL-12p70. When hepatocellular carcinoma cells (HCCs) and macrophages were co-cultured, it was observed that PAP-1a inhibited the growth of Hep-G2, Hep-3B, and Huh7 via immunoregulation. It triggered cell apoptosis by blocking the cell cycle in the G0/G1 stage. Furthermore, PAP-1a had no direct cytotoxicity against the hepatocyte cell line L02 and macrophages RAW264.7.